Cap polyposis occurring in the postoperative course of pelvic surgery. Issue 11 (November 1994) - Géhénot, M; Colombel, J F; Wolschies, E; Quandalle, P; Gower, P; Lecomte-Houcke, M; Van Kruiningen, H; Cortot, A
Abstract : The case is reported of a 42 year old woman who presented with the characteristic clinical, sigmoidoscopic, and histological features of cap polyposis occurring in the postoperative course of pelvic surgery. Pathogenesis of cap polyposis is unknown. In this patient, abnormal colonic motility was not a likely aetiological factor as suggested in previous cases. Despite some arguments favouring an infectious origin or participation, no specific viral or bacterial agent was identified. Cap polyposis remains a poorly recognised condition, which may be confused with inflammatory bowel disease.